Evaluation of the antibacterial and antifungal properties of oleuropein, olea Europea leaf extract, and thymus vulgaris oil - Fuad Al-Rimawi; Mahmood Sbeih; Mousa Amayreh; Belal Rahhal; Samer Mudalal (BMC, 2024)
Abstract Background Although synthetic preservatives and antioxidants may have high antimicrobial and antioxidant activity, they are usually associated with adverse effects on human health. Currently, there is a growing interest in natural antimicrobial and antioxidant agents. This study aimed to evaluate the antimicrobial activity of two medicinal plant extracts and one active compound. Olive leaf extracts (0.2, 0.3, and 0.4% w/v), oleuropein (0.2, 0.4, and 0.6% w/v), thyme oil (0.1%), and oleuropein in combination with thyme oil (0.4% w/v and 0.1% v/v) were used against three bacterial strains (Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus) and two fungal strains (Candida albicans and Aspergillus niger). Results The use of oleuropein resulted in complete antimicrobial activity against Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli. In this context, a reduction of 7 logs was achieved during the storage period (4 weeks). Oleuropein showed no fungal activity at low concentrations (0.2%), but Aspergillus niger was reduced by 2.35 logs at higher concentrations (0.6% w/v). Similar antibacterial and antifungal properties were observed for the olive leaf extracts. Oleuropein at a concentration of 0.4 w/v and a mixture of oleuropein and thyme at concentrations of 0.4 and 0.1 (v/v) showed strong antimicrobial activity against the studied microorganisms. Conclusion Olive leaf extract, thyme oil, and oleuropein have strong antibacterial and weak antifungal properties. There was a good synergistic effect between oleuropein and thymol.